If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2x-3)=3(2-5x)
We move all terms to the left:
2(2x-3)-(3(2-5x))=0
We add all the numbers together, and all the variables
2(2x-3)-(3(-5x+2))=0
We multiply parentheses
4x-(3(-5x+2))-6=0
We calculate terms in parentheses: -(3(-5x+2)), so:We get rid of parentheses
3(-5x+2)
We multiply parentheses
-15x+6
Back to the equation:
-(-15x+6)
4x+15x-6-6=0
We add all the numbers together, and all the variables
19x-12=0
We move all terms containing x to the left, all other terms to the right
19x=12
x=12/19
x=12/19
| -7c-3=11 | | -12+6=3x+5x | | 5c+1+3c=17 | | 5(w+2)=-3w-46 | | 9x+1x-5x=6x5 | | 7u-12=-3(u-6) | | 2x+13/4=2 | | -4(x+9=2x-6 | | 3=t+11.5-7 | | 5m+16=8m-2 | | 6(y-3)=-4y-48 | | 2/x^2-9-3x/x+3=1-3x/x-3 | | 4(y-5)-2y=-8 | | 6(u+3)+6u=6 | | -27=4w-3 | | -1+25x=137x-1 | | -9y-37=-7(y+3) | | |2x-3|=|4x-7x| | | 2=8+3x | | 3(b−13)−11=-5 | | 6y-3/3y+9=1/3 | | 3=y/19/2 | | 4(x+2)=3(2-5x) | | -2(u+6)=6u-5+2(2u+1) | | -3x+6(-5)=-3 | | 4(v+7)=2(3v-8)+2v | | -3(-7y+5)-3y=6(y-3)-7 | | 160+10x=1280−6x160+10x=1280-6x | | -2x-3=x-9 | | 1=t−17 | | 9u-42=6(u-3) | | 3+2x/4=2 |